Study of muscular skeletal apparatus’s functional state of junior sportsmen-power lifters, who have backbone verterbral abnormalities - Ilmatov, V.R. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Purpose: determination of abnormalities and disorders of muscular skeletal apparatuses’ status of power lifters, who have vertebral abnormalities of backbone. Material: 58 junior sportsmen participated in the research. 36 sportsmen were the main group of the research and had vertebral disorders in backbone. For posture testing visual examination was used. Backbone mobility was tested with goniometry method. Flat feet were registered with plantography method. Results: we determined posture abnormalities in sagittal and frontal planes; feet flat, limited maximal movements in thoracic and lumbar spines. It was determined that the most limited were rotational movements and backbone unbending. The next were side bents. These limitations were accompanied by pain syndrome. These observations indirectly confirmed theory of direct interaction of backbone structures with nervous structures. It is also a confirmation of vertebral abnormalities’ presence in junior sportsmen. Conclusions: it was found that in junior sportsmen - power lifters with backbone pathologies in 100% of cases symptoms are determined by local limitations of backbone mobility with pain syndrome. In 35% of cases they are accompanied by posture’s disorders and feet flat. Orientation and methodic of rehabilitation of such sportsmen have been determined.